Radiographic evaluation of the mental foramen in a selected Iranian population - Haghanifar Sina; Rokouei Mehrak (Indian Journal of Dental Research, 2009)
Background: Information on the position of the mental foramen is important for dental surgeons. Variations in its position can be a cause of complications during local anesthesia or surgical procedures. The usual position of the mental foramen in an Iranian population has not been previously reported. Aims: The purpose of this study was to determine the most common location of the mental foramen in an Iranian population. We also analyzed gender differences and the symmetry of location within individuals. Materials and Methods : 400 panoramic radiographs were evaluated with regard to the location and symmetry of the mental foramina in male and female subjects. Results : We found that the mental foramen was located between the first and second premolars in 47.2% of patients and in line with the second premolar in 46%. In 49.2% of males, the mental foramen was in line with the second premolar. In 50.9% of females it was between the first and second premolars. It was symmetrical in 85.7%. Conclusions : Based on this study it appears that the most common position of mental foramen is either between the two premolars or in line with the second premolar. This is in concordance with previous studies.